How perceived discrimination and trust dynamics influence social integration in acculturation and reacculturation: the case of Chinese international student returnees - Le, Tam-Tri; Jin, Ruining (Frontiers in Psychology, 2025)
BackgroundWhen coming to a new social environment, many people unfortunately are under the mental burden of perceived discrimination. The Chinese international student returnees in the post-COVID-19 era present a special case where they experienced considerable discrimination issues during both the processes of acculturation in the host countries as well as reacculturation after returning to China. This study aims to investigate group-based influences on the impacts of discrimination-related perceptions toward social integration (and reintegration) degrees through different psychological pathways of trust.AnalysisEmploying Bayesian analyses aided by Markov Chain Monte Carlo (MCMC) algorithms on survey data of 1,014 Chinese international student returnees, the study examines the multi-layered influences of perceived discrimination and trust (both generalized and personalized) on social integration.FindingsWe found that in the foreign social environment, interestingly, the degree of acculturation and perceived discrimination has a positive association. Generalized trust positively moderates this association while personalized trust has a negative moderating effect. In the domestic social environment, perceived discrimination is positively associated with the degree of negative mental health induced by concerns about whether to stay in China or emigrate. Generalized trust positively moderates this association, while personalized trust negatively moderates it.ConclusionThe findings suggest the possible information exchange pathways where different types of trust and group-based perceptions interact.